Ammonia and Ammonium Exposure of Basil (Ocimum basilicum L.) Growing in an Organically Fertilized Peat Substrate and Strategies to Mitigate Related Harmful Impacts on Plant Growth - Frerichs, Christian; Daum, Diemo; Pacholski, Andreas Siegfried (Frontiers in Plant Science, 2020)
Organic pot-based production of basil (Ocimum basilicum L.) often has lower biomass yield than conventional cultivation. Previous investigations indicate that this growth impairment is related to high ammonium (NH4+) concentrations in the growing media released by the mineralization of organic nitrogen (N) fertilizers. However, as a result of this ammonification process substrate pH may also increase. Under neutral to alkaline conditions NH4+ is converted to ammonia (NH3), which is known to be phytotoxic even at low concentrations. Therefore, we investigated the impact of both ammonical N species on basil grown in a peat substrate. In total three fertilization pot experiments were conducted in a greenhouse in order to compare the effect of different organic base dressings [250 and 750 mg N (L substrate)-1 mainly supplied by a liquid amino acid fertilizer (AAF)] and two initial substrate pH levels (5.5 and 6.5). In two treatments 5% (v/v) mature compost was mixed into the peat one day and twelve days before the substrate was used for sowing, respectively. The aim of this procedure was to stimulate nitrification in this way to reduce ammonical N concentration. Ammonia concentration in the aerial plant surrounding environment was measured by using NH3 detector tubes in combination with an open-top chamber method. The results showed that the growth of basil (number of plants, fresh matter yield, plant height) was significantly inhibited in the second and third week of cultivation by rising NH3 and NH4+ exposure, as well as by a substrate pH ≥ 7.0. These adverse effects were reduced by lowering the organic base dressing rate and adjusting the initial substrate pH to 5.5. Furthermore, the addition of mature compost to peat in combination with a 12-day storage was proven to be effective for promoting nitrification in the organically fertilized substrate. As a result, plant growth was improved by both lower NH3 and NH4+ exposure as well as a faster supply of nitrate (NO3) as an additional N source. Using this approach, it was possible to feed organically fertilized basil right from the seedling stage with a NO3-N/NH4+-N-balanced and later on providing a predominant NO3-N supply.